GAMBARAN PELAYANAN KESEHATAN PUBLIC SAFETY CENTER 119 - Siti Musyarofah; Ratna Muliawati; Mushidah Mushidah (Jurnal Ilmiah Permas: Jurnal Ilmiah STIKES Kendal, 2019)
ABSTRACT Smart city is a concept of city’s development and management with Information and Communication Technology (ICT) to connect, monitor, and control various resources within the city more effectively and efficiently to maximize services to citizens and support sustainable development. The application of PSC 119 SIAGA Kendal District is one of the programs towards Kendal smart city in the health sector. The purpose of this study was to determine the description of the PSC 119. This research is a descriptive study with a survey method. Data was collected using in-depth interview technique to the responsible person and the program implementer. This application was launched in November 2018. This application facilitate citizens to get ambulance and emergency services. Applications can be downloaded at Play Store. In this application provides information on the availability of health service rooms in Kendal, availability of blood from PMI and information about health. It also can report accidents, crime, and fire. The public has not been maximally familiar with 119 SIAGA services. Hopefully that health workers can socialize optimally to the public and the public can take advantage of the applications and services available. Keywords: PSC 119 SIAGA, Kendal Distric, Smart city